AB0480 Colchicine reduces relapse of acute neurological attacks in behcet's disease. (23rd January 2014) - Hirohata, S.; Kikuchi, H.; Sawada, T.; Nagafuchi, H.; Kuwana, M.; Takeno, M.; Ishigatsubo, Y.
Abstract : Background: Acute neurolo-Behcet's disease (NBD) is characterized by acute attacks of meningoencephalitis with or without focal lesions, responding to corticosteroid therapy, and is usually self-limiting, although recurrence of the attacks is sometimes seen. Objectives: In the current studies, we investigate the effects of various factors on the relapse rate in patients with acute NBD. Special attention has been paid to the influences of the cessation of cyclosporine A as well as the use of various immunosuppressants and colchicine. Methods: In a retrospective cohort of 144 patients obtained from a multicenter retrospective survey on BD patients who met the international classification criteria for Behcet's disease and presented any neurological manifestations between 1988 and 2008, 61 patients had attacks of acute NBD. We assessed factors associated with relapses of acute neurological attacks in these 61 patients. Results: Twenty of 61 patients were taking CyA at the onset of acute NBD. All the 20 CyA (+) patients and 34 of the 41 CyA (-) patients had eye involvement. There were no significant differences in demographic features, clinical symptoms, MRI findings, the need for and response to corticosteroid therapy including pulse therapy between CyA (+) patients and CyA (-) patients. Of note, CyA (+) patients showed significantly less relapse rates than CyA (-) patients (HR:0.1177, 95%CI:0.0064-0.6027, p=0.0064). Colchicine appeared to reduce the relapse rates in 61 patients with acute NBD, although it did not reach the statistical significance (HR:0.1177, 95%CI:0.0064-0.6027, p=0.0064). However, colchicine significantly reduced the relapse rates in 41 CyA (-) patients (HR:0.1758, 95%CI:0.0093-0.9728, p=0.0457 on multivariate analysis), whereas methotrexate (HR:1, 2093, 95%CI:0.0628-7.2624, p=0.8653) and azathioprine (HR:1.8814, 95%CI:0.2845-7.4039, p=0.4532) did not show any significant effects on relapses in these patients. Conclusions: These results indicate that CyA-related acute NBD is characterized by the paucity of relapse on discontinuation of CyA compared with CyA-unrelated acute NBD. The data also demonstrate that colchicine is effective to prevent relapses of acute neurological attacksespecially in patients who developed acute NBD in the absence of CyA. References: Hirohata S, Kikuchi H, Sawada T, Nagafuchi H, Kuwana M, Takeno M, Ishigatsubo Y. Clinical characteristics of neuro-Behcet's disease in Japan: a multicenter retrospective analysis. Mod Rheumatol 22: 405-13, 2012. Akman-Demir G, Ayranci O, Kurtuncu M, Vanli EN, Mutlu M, Tugal-Tutkun I. Cyclosporine for Behçet's uveitis: is it associated with an increased risk of neurological involvement? Clin Exp Rheumatol. 2008; 26(Suppl 50): S84-90. Disclosure of Interest: None Declared